Análise dos meios de comunicação interna em uma instituição de ensino: um estudo de caso do CEFET - NI - Oliveira, Suzana Carneiro de (2013)
The world today lives a context of globalization of information that need to be shared quickly. Internal communication in organizations emerges as an important issue that needs to be analyzed and managed strategically. This research aimed to develop a case study on the internal communication of the administrative sectors of a Public Federal Technological Education, located in Nova Iguaçu. We performed an exploratory research - descriptive, using as a data source direct observation and interviews. The collection and analysis of data, allowed the construction of a diagnosis of the reality of the organization 's focus on quality of communication, identification of communication resources used to convey the principles and institutional values the mapping of existing channels of communication and the efficiency of these. The study speaks to the theme of communication theory, highlighting its concepts, tools and use the internal environment of the organization, parallel to organizational, governance and culture. The data demonstrated that the majority of the investigated communication establishment occurs spontaneously through informal initiatives from the servers themselves, generally through mechanisms insufficient and most often inappropriate time having failures occurring frequently. Thus, we propose the challenge managers to rethink the internal communication as a tool for strategic differentiation for successful institutional objectives and the need for effective management of communicative acts , so as to make them a feature of cultural interaction to accompany speed of change , effectively investing in the development of process quality